REGULATION AND VALIDITY OF UNDERAGE MARRIAGE IN THE PERSPECTIVE OF INDONESIAN CIVIL LAW - Lindri Purbowati; Zainal Arifin Hoesein (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2026)
Underage marriage is a legal issue that still frequently occurs in Indonesia despite the existence of regulations on the minimum age for marriage. This study aims to analyze the regulation and validity of underage marriage in the perspective of Indonesian civil law and its legal implications for child protection. The research method used is normative empirical legal research with a regulatory and conceptual approach. The results of the study show that Law Number 16 of 2019 has set a minimum age for marriage for men and women, but the existence of a marriage dispensation mechanism provides legal space for underage marriage to occur. From a civil law perspective, such marriages are still considered valid if they obtain court permission and have the same civil law consequences as marriages in general. However, the practice of marriage dispensation still shows the weak application of the principles of child protection and substantive justice. Therefore, it is necessary to strengthen legal regulations and consider the best interests of the child in every marriage dispensation decision. Keywords: underage marriage; civil law; marriage dispensation.